1990
DOI: 10.1016/s0006-3495(90)82382-1
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of single phospholipid bilayers adsorbed to micro glass beads. A new vesicular model system studied by 2H-nuclear magnetic resonance

Abstract: Spherical supported vesicles (SSVs), a new model system consisting of single dimyristoyl phosphatidylcholine (DMPC) bilayers adsorbed to spherical glass beads with a narrow size distribution, were prepared at two different sizes (0.5 and 1.5 microns) and their physical properties were studied by deuterium nuclear magnetic resonance (2H-NMR). Such SSV samples can be prepared at any desired size between 0.3 and 10 microns. The 2H-NMR measurements provide evidence for a strong dependence of the spectra and the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
391
2
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(406 citation statements)
references
References 15 publications
12
391
2
1
Order By: Relevance
“…Previously, we demonstrated that purified SpoVM-GFP selectively bound to lipid vesicles similar in size to the forespore in a mixture of giant unilamellar vesicles of various sizes (24). In the current investigation, we eliminated limitations associated with giant unilamellar vesicles (variability in vesicle size and associated variability in membrane stiffness) by using SSLBs, in which a single phospholipid bilayer is assembled on the surface of silica beads of defined size (29,30). In addition to providing a more strictly defined membrane radius of curvature (determined by the diameter of the silica bead), the use of a supported bilayer system eliminates osmotic-dependent variability in membrane tension across vesicle curvatures (31).…”
Section: Resultsmentioning
confidence: 89%
“…Previously, we demonstrated that purified SpoVM-GFP selectively bound to lipid vesicles similar in size to the forespore in a mixture of giant unilamellar vesicles of various sizes (24). In the current investigation, we eliminated limitations associated with giant unilamellar vesicles (variability in vesicle size and associated variability in membrane stiffness) by using SSLBs, in which a single phospholipid bilayer is assembled on the surface of silica beads of defined size (29,30). In addition to providing a more strictly defined membrane radius of curvature (determined by the diameter of the silica bead), the use of a supported bilayer system eliminates osmotic-dependent variability in membrane tension across vesicle curvatures (31).…”
Section: Resultsmentioning
confidence: 89%
“…We have previously demonstrated that Compound 5 (Cpd 5) is capable of capturing active γ-secretase complexes under native conditions (28). We fused the PS1ΔE9 proteoliposomes with silica microspheres to form assemblies in which the lipid bilayer is separated from the silica surface by a 1-2 nm water layer (29), and termed these PS1ΔE9 proteolipobeads. Binding of Cpd 5 to the beads should mimic the assemblies as inhibitor-γ-secretase bimolecular complex.…”
Section: Resultsmentioning
confidence: 99%
“…It is known from the literature that a supported PC bilayer on glass or silica binds a certain amount of water to the lipid head groups facing the solution (36,37). The latter is another candidate reason for the protein resistance of PC head groups (4).…”
Section: Discussionmentioning
confidence: 99%